DOUBLE BURDEN OF COVID19 PANDEMIC TO PREGNANT WOMAN EARLY DETECTION WITH HBSAG IN INDONESIA - Lasut, Doni; Hermawan, Asep (Muhammadiyah International Public Health and Medicine Proceeding, 2022)
The COVID-19 pandemic has heterogeneously affected the use of essential health services worldwide, with disruptions in some countries beginning in the early stages of the emergency in March 2020. These disruptions have occurred on both the supply and demand sides of healthcare and have often been related to resource shortages to provide care and lower patient turnout associated with mobility restrictions and fear of contracting COVID-19 at facilities. The goal of this paper, compare the HBsAg test before and after the COVID-19 pandemic to a pregnant woman's early detection with HBsAg to achieve the target of at least 80% in 2020. Method using a simple mathematical calculation modeling approach developed to predict health service use until the pandemic using routinely collected health information systems data (SIHEPI). Results show HBsAg reactive Proportion of total pregnant women in each Province is about 2,1% on 47,91% of pregnant women in Indonesia, highest in eastern Indonesia province (NTT, Papua, and West Papua). With a calculation of 80% targeted a pregnant woman in 2020, reactive Proportion predicted about 4,4% in Indonesia, West Papua becomes the highest Province with 21,38%, Papua about 12,63%, and NTT about 11,31%. In conclusion, refered to comparison of mathematical calculation approach from 80% targeted average become 4,4% reactive HBsAg test. Delaying early detection in pregnant women before and after the covid19 pandemic becomes a double burden in Indonesia. These phenomena become a high-risk factor for maternal-to-child transmission. Indonesia needs serious action to achieve Hepatitis B elimination in 2030.